2015
DOI: 10.1177/1971400915598075
|View full text |Cite
|
Sign up to set email alerts
|

Complex aortic arch anomaly: Right aortic arch with aberrant left subclavian artery, fenestrated proximal right and duplicated proximal left vertebral arteries—CT angiography findings and review of the literature

Abstract: Congenital aortic arch and vertebral artery anomalies are a relatively rare finding discovered on imaging either incidentally or for evaluation of entities like dysphagia or subclavian steal. Right aortic arch is an uncommon anatomical anomaly that occurs in less than 0.1% of the population, and in half of these cases the left subclavian artery is also aberrant.(1) Unilateral vertebral artery (VA) duplication is rare with an observed prevalence of 0.72% in cadavers.(2) Fenestration of the VA is more common tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 28 publications
0
21
0
2
Order By: Relevance
“…There may also be fenestration or duplication of vertebral artery origins. These variations may have no clinical significance, but they should be documented as they may have certain surgical implications (30). ARSA is the most common anomaly associated with left aortic arch and is predominant in females (31).…”
Section: Vertebral Artery Origin Variationsmentioning
confidence: 99%
“…There may also be fenestration or duplication of vertebral artery origins. These variations may have no clinical significance, but they should be documented as they may have certain surgical implications (30). ARSA is the most common anomaly associated with left aortic arch and is predominant in females (31).…”
Section: Vertebral Artery Origin Variationsmentioning
confidence: 99%
“…El tratamiento es quirúrgico y el enfoque exacto depende de la anatomía, síntomas, tamaño y presencia concomi tante de un aneurisma aórtico torácico [7].…”
Section: Revista Médica De Panamáunclassified
“…However, a more recent study showed that while 71.2% of their 141 ARSA cases reported dysphagia as a symptom, only 19.2% (27/141) possessed the bicarotid morphology [8]. In addition, in many cases of a BCT co-occurring with an ARSA, barium-contrast examination indicates that the esophagus is compressed posteriorly and obliquely at the level of the aorta [3,4,6,9,15,[18][19][20], suggesting that the ARSA is the primary contributor to esophageal compression and resulting dysphagia. There are also documented cases in which a BCT is absent or extremely mild, but dysphagia still presents [19,21].…”
Section: Coexisting Malformations Of the Aberrant Right Subclavian Armentioning
confidence: 99%